PEMERIKSAAN JAMUR PADA ROTI ISI KACANG HIJAU YANG DIPERJUALBELIKAN DI PASAR SEI SIKAMBING MEDAN - Sinaga, Eka Margaretha; Nasution, Pandapotan; Maimunah, Siti; Yanti, Surfin Putri (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Green-bean filling bread is made from wheat flour and water and fermented with yeast. The presence of carbohydrates and sugar in bread causes mold to grow. This examination aims to determine the presence or absence of fungus on green bean sandwiches according to the SNI standard with no more than 104 microbial ingredients. The medium used in this examination is Potato Dextrose Agar (PDA) which has been added with 0.1% chloramphenicol. This examination uses an experimental method (parametric experiment). The sample in this examination is green bean stuffed bread traded in the Sei Sikambing market in Medan, the number of samples examined is 4 types from 2 shophouses in the Sei Sikambing market, Medan in 2015. The results of the examination showed the presence of fungal growth in all samples so the sample does not meet the requirements of SNI. To consume bread, you should pay attention to the condition of the bread at the time of buying.